Kinetics of Thermal-Induced Physical Quality Alterations in Chicken Meat Processing - Nadya Klaresza Audrey; Eko Hari Purnomo; Nur Wulandari (The University of Lampung, 2026)
Thermal processing of food often leads to a reduction in quality, highlighting the need to optimize heating conditions based on the kinetics of quality changes. This study investigated the physical quality of chicken meat—including cooking loss, water-holding capacity, texture, and color—during heating in a water bath (75 and 95 °C) and a pressure cooker (110 °C) for defined durations and modeled the kinetics of these changes. Heat distribution tests confirmed uniform temperatures, as indicated by minimal differences between thermocouples and the cold spot, while heat penetration tests ensured thorough heating, with lag times of 18.25 ± 2.25, 16.13 ± 4.58, and 19.25 ± 4.77 minutes at 75, 95, and 110 °C, respectively. Changes in physical quality at constant temperatures followed first-order reaction kinetics, and the temperature effect was described using the Arrhenius equation. The Arrhenius model revealed that higher temperatures accelerated the rate of quality changes, resulting in increased cooking loss, shear force, L*, and browning index, whereas water-holding capacity and cohesiveness decreased. Comparison of the D and Z values for physical quality parameters with those of Clostridium botulinum spores (D121.1 °C = 0.22 min, Z = 10 °C) suggested that high-temperature, short-time treatments could minimize detrimental changes in chicken meat while effectively inactivating target microorganisms.